Synthesis of dynamic g-C3N4/Fe@ZnO nanocomposites for environmental remediation applications. Issue 14 (1st October 2020) - Qamar, Muhammad Azam; Shahid, Sammia; Javed, Mohsin
Abstract: An effective g-C3 N4 /Fe@ZnO heterostructured photocatalyst was synthesized by a simple chemical co-precipitation method and characterized by X-ray diffraction, Fourier transform infrared spectroscopy, transmission electron microscopy and ultraviolet–visible spectroscopy. Transmission electron microscopy revealed that 7-8 nm-sized 1%Fe@ZnO nanoparticles were evenly distributed on g-C3 N4 nanosheets to form a hybrid composite. The photocatalytic effectiveness of the composites was assessed against methylene blue dye, and it was found that the 50%g-C3 N4 /Fe@ZnO photocatalyst was more efficient in harvesting solar energy to degrade dye than the ZnO, 1%Fe@ZnO, g-C3 N4, g-C3 N4 /ZnO and (10, 25, 40, 60 & 75 wt%) g-C3 N4 /Fe@ZnO samples. The antibacterial competency of the samples was also explored against Gram-positive ( Bacillus subtilis, Staphylococcus aureus and Streptococcus salivarius ) and Gram-negative ( Escherichia coli ) bacteria through the well diffusion method. The 50%g-C3 N4 /Fe@ZnO nanocomposite exhibited a superior antibacterial action compared to that of the rest of the samples. The exceptionally improved photocatalytic and antimicrobial efficiency of the 50%g-C3 N4 /Fe@ZnO composite was primarily accredited to the synergic outcome of the interface established between Fe@ZnO nanoparticles and g-C3 N4 nanosheets.